2020
DOI: 10.1093/mnras/staa1712
|View full text |Cite
|
Sign up to set email alerts
|

Scatter in Sunyaev–Zel’dovich effect scaling relations explained by inter-cluster variance in mass accretion histories

Abstract: ABSTRACT X-ray and microwave cluster scaling relations are immensely valuable for cosmological analysis. However, their power is limited by astrophysical systematics that bias mass estimates and introduce additional scatter. Turbulence injected into the intracluster medium via mass assembly contributes substantially to cluster non-thermal pressure support, a significant source of such uncertainties. We use an analytical model to compute the assembly-driven non-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 160 publications
2
14
0
Order By: Relevance
“…Recent progress in modeling subhalo orbital evolution has demonstrated the importance of accounting for the evolution of the host halo potential (Ogiya et al 2021), and so deploying our model in this context could be leveraged to capture physically realistic accretion-rate correlations in the halo-to-halo variance of substructure abundance and orbits across cosmic time (see, e.g., Jiang & van den Bosch 2017). Along similar lines, it has recently been shown that scatter in the thermal Sunyaev-Zel'dovich effect is largely driven by variance in the assembly histories of cluster-mass halos (Green et al 2020), and so our model may also help improve the predictive power of models for the massobservable relation of galaxy clusters.…”
Section: Discussion and Future Worksupporting
confidence: 53%
“…Recent progress in modeling subhalo orbital evolution has demonstrated the importance of accounting for the evolution of the host halo potential (Ogiya et al 2021), and so deploying our model in this context could be leveraged to capture physically realistic accretion-rate correlations in the halo-to-halo variance of substructure abundance and orbits across cosmic time (see, e.g., Jiang & van den Bosch 2017). Along similar lines, it has recently been shown that scatter in the thermal Sunyaev-Zel'dovich effect is largely driven by variance in the assembly histories of cluster-mass halos (Green et al 2020), and so our model may also help improve the predictive power of models for the massobservable relation of galaxy clusters.…”
Section: Discussion and Future Worksupporting
confidence: 53%
“…As discussed in detail in , this halo-tohalo variance is predominately driven by variance in the halo mass accretion histories (see also e.g. Giocoli et al 2010;Green et al 2020). The second-order f sub also increases with M 0 , has much larger log-scatter than the total f sub , and its mean is smaller by a factor of ≈15−30.…”
Section: Mass-dependence and Halo-to-halo Variance Of F Submentioning
confidence: 94%
“…Mergers and mass accretion introduce non-thermal pressure support, which reduces the SZ signal detected. Thus, at fixed mass, the higher the mass accretion rate, the higher the non-thermal pressure fraction and the smaller the 𝑌 𝑆𝑍 value (Nelson et al 2014b;Green et al 2020). Thus, in general, we expect a negative correlation between the residual of the 𝑌 𝑆𝑍 − 𝑀 relation and the mass accretion rate.…”
Section: Reproducing the 𝑌 𝑆𝑍 − 𝑀 Relationmentioning
confidence: 90%
“…4, the relations of the respective cluster populations have slope and scatter within 1% of each other. For context, previous semi-analytic models which only take into account mass accretion but not baryonic physics and clumpy accretions like major mergers (Green et al 2020) reproduced 70% of the intrinsic scatter when compared to non-radiative simulations, and reproduced just 1/3 to 1/2 of the scatter when compared to full-physics simulations.…”
Section: Reproducing the 𝑌 𝑆𝑍 − 𝑀 Relationmentioning
confidence: 95%
See 1 more Smart Citation